A Case Study Of Strategies And Management Of Coca-Cola Company In United States - Ngian, Seng Yaw (2005)
This thesis deals with the strategic and the management skills of the company. Coca Cola Company has to play an important role in changing their strategies to cater the increasing internal and external competition in order to sustain its position as the market leader in the soft drinks industry.